Demographic Profile and Illness Symptoms of Artisanal Gold Miners in Ujung Padang Rasian Health Center Area, South Aceh - Lensoni, Lensoni; Putri, Rosalia; Rosdiana, Eka; Rizki, Muhammad; Diffa , Farah; Karma, Taufiq; Nurdin, Ambia (Gema Lingkungan Kesehatan, 2025)
ABSTRACT This study aims to analyze the relationship between demographic characteristics and clinical symptoms experienced by artisanal gold mine workers due to mercury exposure at the UPTD Rasian Ujung Padang Community Health Center Work Area, South Aceh District, Aceh Province. A quantitative descriptive design with a cross-sectional survey approach was employed. The results showed that the most commonly reported chronic toxicity symptoms were headaches (34 respondents), coughing and pain during urination (24 respondents), pelvic pain (23 respondents), and nausea (22 respondents). Regarding acute toxicity symptoms, the majority of respondents experienced muscle cramps (17 respondents), headaches (16 respondents), irritability (3 respondents), and insomnia (2 respondents). Correlation tests indicated that gender was not significantly associated with disease symptoms (p-value = 0.66 > 0.05), while age (p-value = 0.00 < 0.05), education level (p-value = 0.00 < 0.05), and length of employment (p-value = 0.01 < 0.05) showed significant associations. In conclusion, age, education level, and length of employment were significantly associated with the clinical symptoms experienced by artisanal gold mine workers.